Addiction Counselor Profession: Perception of Family Support for Recovering from Drug Abuse Addiction - Supriyanto, Agus; Hendiani, Nurlita; Hartini, Sri; Sabri, Farhana (Universitas PGRI Madiun, 2021)
The family is the smallest unit of society that affects the lives of drug users undergoing rehabilitation programs. Family can be a source of social support for substance users in solving problems through perception. The perception of family support is a source of social support to foster confidence in drug rehabilitation programs. This study aims to determine the level of family support for substance users undergoing drug rehabilitation programs and recommendations for individual, group, and family counselling services. This study used a descriptive research type with the subject N = 217. The research subjects consisted of male and female genders; the data analysis used quantitative descriptive analysis. The results showed that the category of substance users' perceptions of family support had a low level. The types of users at a deficient level were 2.30%, the low level was 57.14%, the high level was 33.18%, and the very high level was 7.37%. These findings prove that the family's influence is still very minimal for users to recover during rehabilitation. The contribution of family perceptions supports beliefs about recovering from drug addiction. The addiction counsellor profession from guidance and counselling graduates needs to implement family counselling services in collaboration with families in developing perceptions of drug addicts. Recommendations from this study's results are the implementation of family counselling services and support from families in concrete, emotional, informational, and reward.